Development of Hypercontent E-Modules For Optimizing Learning in Atelier Clothing Business - Rahma Dewi, Eka; Hanim, Halidah; Rambe, Armaini (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
Learning in the fashion atelier business requires students to integrate competencies in business management, customer service, and professional sewing techniques. However, limited class time and the lack of interactive media often hinder students’ ability to learn independently and apply these skills effectively. This study developed a hypercontent-based e-module integrated with job sheets to enhance independent learning in the Fashion Atelier Business course. The research employed the ADDIE model (Analyze, Design, Develop, Implement, Evaluate) as a systematic development framework. Validation results showed high feasibility: material experts = 89% and media experts = 93%, both categorized as “very good.” User trials yielded positive responses, with scores of 88.5%, 91.2%, and 94.6% for small, medium, and large groups, respectively. These results indicate that the e-module is valid, practical, and effective for vocational learning. The novelty of this study lies in the integration of hypercontent elements with practical job sheets, offering an interactive and self-paced digital learning experience that bridges theory and practice. This innovation supports students’ entrepreneurial readiness and aligns vocational education with Industry 4.0 learning needs, providing a model for technology-enhanced fashion education.